2021
DOI: 10.1021/acscatal.0c04504
|View full text |Cite
|
Sign up to set email alerts
|

Formation Mechanism of the Co2C Nanoprisms Studied with the CoCe System in the Fischer–Tropsch to Olefin Reaction

Abstract: Cobalt carbide (Co2C) nanoprisms are efficient for olefin production via Fischer–Tropsch to olefin (FTO) reaction. However, these Co2C nanoprisms can only be prepared from the given CoMn composite oxide precursor with a sodium promoter and the formation mechanism remains ambiguous up to now. In the present work, the Ce-stabilized spherical Co nanoparticles were synthesized and were used as a precursor to study the formation mechanism of the active phase. The experimental results and theoretical analysis showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Suitable metal–supporter interaction with CNTs and surface-passivated SiO 2 as support favored the formation of CoMn composite oxides. , Smaller Co x Mn 1– x O possessing a higher concentration of oxygen vacancies promoted CO dissociation to form active C* species and produced a higher proportion of Co 2 C nanoprisms, leading to an enhancement of the FTO reactivity . In addition, the suitable reduction conditions and mild reaction pressure also have a profound influence on the morphology control of Co 2 C nanostructures. , It is noteworthy that a very recent work from Li et al suggested that the Mn promoter can be replaced with Ce, which worked as facet stabilizers that can reduce the surface energy of the Co 2 C nanostructures and change the relative growth rates of the Co 2 C crystal in various orientations …”
Section: Fischer–tropsch To Olefinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Suitable metal–supporter interaction with CNTs and surface-passivated SiO 2 as support favored the formation of CoMn composite oxides. , Smaller Co x Mn 1– x O possessing a higher concentration of oxygen vacancies promoted CO dissociation to form active C* species and produced a higher proportion of Co 2 C nanoprisms, leading to an enhancement of the FTO reactivity . In addition, the suitable reduction conditions and mild reaction pressure also have a profound influence on the morphology control of Co 2 C nanostructures. , It is noteworthy that a very recent work from Li et al suggested that the Mn promoter can be replaced with Ce, which worked as facet stabilizers that can reduce the surface energy of the Co 2 C nanostructures and change the relative growth rates of the Co 2 C crystal in various orientations …”
Section: Fischer–tropsch To Olefinsmentioning
confidence: 99%
“…115,116 It is noteworthy that a very recent work from Li et al suggested that the Mn promoter can be replaced with Ce, which worked as facet stabilizers that can reduce the surface energy of the Co 2 C nanostructures and change the relative growth rates of the Co 2 C crystal in various orientations. 117 Similar to Fe-based FTO catalysts, Co 2 C-based catalysts also suffer from high CO 2 selectivity (>40%) and low carbon efficiency. Very recently, Lin et al developed a hydrophilic silica-coated CoMn-based catalyst for the FTO reaction, and CO 2 selectivity was largely suppressed from 44.7% to 15.1%, while enhancing olefin selectivity in total products from 39.7% to 58.8% (Figure 9a).…”
Section: Fischer−tropsch To Olefinsmentioning
confidence: 99%
“…Notably, it has distinct features in different reaction atmospheres. As for CO-FTS, nanoprism Co 2 C with preferentially exposed (101) and (020) facets has been proven to be responsible for the synthesis of C 2 ~C4 = , while electronic (alkali metal) and structural promoters (Mn and Ce) are instrumental in its morphological control (11)(12)(13)(14)(15). The synthesis of Co 2 C is commonly divided into two steps, including an initial reduction and carburization in syngas (CO and H 2 ) or CO. Wavelet transform and linear combination fitting results of in situ x-ray absorption spectroscopy (XAS) indicate that cobalt oxide (CoO) is first reduced to metallic cobalt (Co 0 ), and then carburized to Co 2 C (16).…”
Section: Introductionmentioning
confidence: 99%
“…Further characterization and theoretical simulation confirmed the exposed facet of ( 101) and (020) on the obtained Co 2 C nanoprisms, which greatly favored olefin production while restraining CH 4 production. Subsequent works have displayed that Na and Mn could act as electronic and structural promoters, respectively, facilitating the formation of Co 2 C with special morphologies [15]. In addition, the reduction condition and cobalt-support interaction have significant impacts on the catalytic behaviors of Co 2 C-based catalysts.…”
Section: Introductionmentioning
confidence: 99%